Case Study of Polymer Concrete Composite for Pre-cast Product Application - Nor Shaufina, Md Jaafar; Omezza Nur Aishah, Omar; Muhamad Soffi, Manda (INTI International University, 2022)
Polymer concrete (PC) is a composite material made by fully replacing the cement binders of conventional cement concrete with polymeric binders. The property of PC is superior to cement concrete in term of curing time, higher strength, bulk modulus, acid or chemical material resistance as well as corrosion, ability to form complex shapes, and excellent vibration damping properties. The purpose of this study is to investigate strength limit of PC specimens with composition variations. In this project, experimental study has been performed on PC with variations of aggregates mixtures and resin ratio. Various composition of PC based on literatures are tested to determine the best composition for pre-cast product application. The study reveals that PC with fine aggregates and 30:70 aggregate resin ratio (AG2RT2) has the highest compressive strength (94.73 MPa) and water proof capacity (0%). Then PC with fine and coarse aggregates, fillers and chopped fibers (AG4RT2) has the highest flexural strength (12.94 MPa). The optimum PC composition specification has been applied to produce pre-cast product and field test has confirmed the product strength and durability. There are three PC pre-cast products that have been produced; plate, grating and drain trench before simple field test applied to observe the products serviceability. All products do not fail in field test within predetermined limit; static loading, free fall and water flow test. The potential to apply PC in existing pre-cast cement concrete product has been proven to enhance the product performance as well as preserving the nature by introducing polymeric resins as a replacement to cement.